2009
DOI: 10.1088/0004-637x/694/2/l107
|View full text |Cite
|
Sign up to set email alerts
|

On the Bl Lacertae Objects/Radio Quasars and the Fr I/Ii Dichotomy

Abstract: In the frame of unification schemes for radio-loud active galactic nuclei (AGNs), FR I radio galaxies are believed to be BL Lacertae (BL Lac) objects with the relativistic jet misaligned to our line of sight, and FR II radio galaxies correspond to misaligned radio quasars. The Ledlow-Owen dividing line for the FR I/FR II dichotomy in the optical absolute magnitude of the host galaxy-radio luminosity (M R -L Rad ) plane can be translated to the line in the black hole mass-jet power (M bh -Q jet ) plane by using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 49 publications
8
55
1
Order By: Relevance
“…Our sample include 66 BL Lacs (28 low-energy-peaked BL Lacs, LBLs, and 38 high-energy-peaked BL Lacs, HBLs) and 146 radio quasars (79 flat-spectrum radio quasars, FSRQs, and 67 steep-spectrum radio quasars, SSRQs)(see Xu et al 2009). Figure 1 show the relation between the black hole (BH) mass, M bh , and jet power, Q jet for both BL Lacs and radio quasars.…”
Section: Unification Of Bl Lacs/radio Quasars and Fr I/iimentioning
confidence: 99%
“…Our sample include 66 BL Lacs (28 low-energy-peaked BL Lacs, LBLs, and 38 high-energy-peaked BL Lacs, HBLs) and 146 radio quasars (79 flat-spectrum radio quasars, FSRQs, and 67 steep-spectrum radio quasars, SSRQs)(see Xu et al 2009). Figure 1 show the relation between the black hole (BH) mass, M bh , and jet power, Q jet for both BL Lacs and radio quasars.…”
Section: Unification Of Bl Lacs/radio Quasars and Fr I/iimentioning
confidence: 99%
“…The FRII have higher average Eddington ratios than FRI radio galaxies. Xu et al (2009) also found that the radio quasars have higher Eddington ratios than BL Lacs. Ghisellini and Celotti (2001) suggested that the FRII have higher accretion rate than FRI. A possible interpretation of this phenomenon is the exhaustion of the gas stockpile available for accretion in the host galaxy (Cattaneo et al 1999;Haehnelt and Kauffmann 2000).…”
Section: The Distributionsmentioning
confidence: 85%
“…Xu et al(2009) got this dividing line log Q jet (ergs −1 ) = 1.13M bh + 33.18 + 1.5 log f (4) in the M bh − Q jet plane (see Wu & Cao 2008 for details). In Figure 6, we plot the relation between the black hole mass and jet power for FSRQs and BL Lacs with f=20.…”
Section: The Distributionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In nearby lowluminosity AGNs, it was also found that broad emission lines and torus are still exist but they are much weaker than luminous Seyfert and QSOs (Tran 2001;Gu & Huang 2002;Laor 2003;Elitzur & Ho 2009;Cao 2010;Hönig & Beckert 2007;Ho 2008, e.g.,). The weaker BLR or torus in low-luminosity AGNs or low-power BL Lacs may be caused by (or coevolved with) the transition standard cold disk to radiatively inefficient accretion flows when accretion rate decreases (e.g., Xu, Cao & Wu 2009;Ghisellini & Celotti 2001;Wang et al 2002;Cao 2003;Wu & Cao 2006). Our results, combined with several former SED modeling of BL Lacs with weak EC components, suggest that BLR or torus may still play a role in Compton scattering in low-power BL Lacs, where BLR/torus may become weak but not fully disappear in these low-power sources (e.g., LLAGNs, FR Is and BL Lacs).…”
Section: Conclusion and Discussionmentioning
confidence: 99%